KARAKTERISTIK BATUAN FORMASI KEREK SEBAGAI RESERVOIR DI LAPANGAN CIPLUK KENDAL - Ikhwannur Adha (PETROGAS: Journal of Energy and Technology, 2021)
Cipluk Field is located in Klantung, Kendal, Central Java. It is an oil field in Indonesia. This field has abandoned status but until now oil seeps are found in the rocks around the field. Based on regional geology by Thanden et al. (1996), the estimated reservoir is Kerek Formation. The formation is exposed around and south of the field, around Lutut River. This research was conducted to determine the rock characteristics of Kerek Formation and to be analog to determine reservoir rock characteristics of the Cipluk Field petroleum system. This research is based on field evaluation data. Data were obtained through direct field investigations aimed at knowing the geological conditions of the research area. The main data used consisted of field observation data, rock samples, SRTM images, seismic data, and well data. Kerek Formation in the study area is divided into three members and only two members are exposed on the surface, Middle Miocene Kerek Formation and Late Miocene Kerek Formation. Middle Miocene Kerek Formation has characteristics with interbedded claystone-sandstone dominantly with limestone on the bottom and dominantly with sandstone on top. This member has a fairly good character as a reservoir for the Cipluk Field petroleum system based on its rock composition and geometry.